The need for consistency in International Investment abbitration awards: a case study of awards rendered under the international centre for settlement of investment disputes - Mbonigaba, Laurent (Centre for Law and Society, 2026)
Legal theory suggests that the rule of law is only the rule of law if it is consistently applied so as to be predictable.2 In common law jurisdictions, predictability is guaranteed by judicial systems through their reliance on precedent (stare decisis) and in civil law traditions through a de facto case Iaw.3 In recent years there has been an increasing number of diverging decisions within the investor-state arbitration system.4 Such discrepancies in the disputes settlement system have the potential to jeopardize the investor-state arbitration system by failing to respond to the expectations of investors and the host states. 5 Besides, a discomfort is felt in the field of international investment arbitration due to the inconsistencies of arbitral awards. Parties to international investment arbitrations have often expressed dissatisfaction with this state of affairs particularly on the lack of an appellate body competent to review investment awards.